2018
DOI: 10.1016/j.physrep.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The BCS–BEC crossover: From ultra-cold Fermi gases to nuclear systems

Abstract: This report adresses topics and questions of common interest in the fields of ultra-cold gases and nuclear physics in the context of the BCS-BEC crossover. By this crossover, the phenomena of Bardeen-Cooper-Schrieffer (BCS) superfluidity and Bose-Einstein condensation (BEC), which share the same kind of spontaneous symmetry breaking, are smoothly connected through the progressive reduction of the size of the fermion pairs involved as the fundamental entities in both phenomena. This size ranges, from large valu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
301
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(310 citation statements)
references
References 486 publications
(990 reference statements)
9
301
0
Order By: Relevance
“…Clearly, the NSR and T matrix approaches are essentially equivalent when the self-energy corrections are small, while when this does not occur, quantitative differences are expected in their results for thermodynamic quantities, such as, e.g., the chemical potential µ and critical temperature T c . For the BCS-BEC crossover in a single band, these differences turn out to be rather moderate across the whole BCS-BEC crossover, even when the self-energy is not small [21]. We will show below that the same occurs in the two band system considered in this work.…”
Section: T Matrix Approximation For Two Band Systemsmentioning
confidence: 59%
See 1 more Smart Citation
“…Clearly, the NSR and T matrix approaches are essentially equivalent when the self-energy corrections are small, while when this does not occur, quantitative differences are expected in their results for thermodynamic quantities, such as, e.g., the chemical potential µ and critical temperature T c . For the BCS-BEC crossover in a single band, these differences turn out to be rather moderate across the whole BCS-BEC crossover, even when the self-energy is not small [21]. We will show below that the same occurs in the two band system considered in this work.…”
Section: T Matrix Approximation For Two Band Systemsmentioning
confidence: 59%
“…As another direction toward the unconventional properties of superconductors, the crossover from the weakly coupled BCS state to the Bose-Einstein condensate (BEC) of a tightly bound molecule with increasing the two body attractive interaction has extensively been discussed [15,16]. In fact, this crossover has been realized in ultracold Fermi atomic gases [17,18], and currently, various properties and fluctuation phenomena of this system have been investigated theoretically and experimentally [19][20][21]. Interestingly, recent experiments of FeSe multi-band superconductors also indicated that this electron system is in the BCS-BEC crossover regime [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Following the standard prescription for the BCS-BEC crossover problem [3], we substitute the bare interaction strength g between the ↑ and ↓ bosons with the associated s-wave scattering length a s in vacuum through the relation 1/g = −mV /(4πa s )+ k 1/(2 k ), where V is the volume. In addition, we define a length scale k 0 through an analogy with the number equation N 0 = k 3 0 V /(3π 2 ) of a free Fermi gas at T = 0, along with the corresponding energy scale 0 = k 2 0 /(2m).…”
Section: Mean-field Theory For the Inter-component Pairingmentioning
confidence: 99%
“…This intrinsic stability is what lies behind the long-sought realization of the so-called BCS-BEC crossover, when a two-component Fermi gas is magnetically swept across a Feshbach resonance [1]. Having witnessed more than a decade of tremendous successes since their creation, the ultra-cold Fermi gases has become a thriving field in modern quantum physics as it keeps enriching its toolbox with a widerange of applications for the strongly-correlated phenomena in a much broader context [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation